INKULTURASI BUDAYA SUMBA DALAM GEREJA KATOLIK DAN SAKRALITAS LITURGI - Konradus Doni Kelen; Kanisius Kami; Arianti Malo (Jurnal Pelayanan Pastoral, 2026)
The liturgy of the Catholic Church is present and rooted in local culture. This is possible because the church's liturgy can only be lived and expressed in local ways. On Sumba Island, the church's liturgy is expressed contextually and inculturatively, as seen in various forms of culture, such as language, music, dance, and clothing. This study aims to determine the people's impressions and feelings about the inculturation movement at the Holy Spirit Cathedral Parish. This research used qualitative methods with an ethnographic approach. Data for this study were obtained through in-depth interviews with informants from several groups. Subsequently, the data were analyzed descriptively and qualitatively. The results show that the practice of liturgical inculturation at the Holy Spirit Cathedral Parish in Weetebula does not diminish the sacredness of the liturgy as long as it is appropriate to its portion and context. Instead, it enriches the congregation's experience of faith, without diminishing the core of the faith as taught in the Catholic Church. The conclusion that can be drawn from this study is that inculturation and liturgical sacredness can coexist and do not negate each other. These findings can serve as pastoral recommendations within the Catholic Church regarding the importance of liturgical inculturation within the church.